Ex vivo expansion in a clinical grade medium, containing growth factors from human platelets, enhances migration capacity of adipose stem cells - Agostini, Francesco; Vicinanza, Carla; Lombardi, Elisabetta; Da Ros, Francesco; Marangon, Miriam; Massarut, Samuele; Mazzucato, Mario; Durante, Cristina (Frontiers in Immunology, 2024)
Adipose tissue mesenchymal stem/stromal cells (ASC) can be used as advanced therapy medicinal product in regenerative and cancer medicine. We previously demonstrated Supernatant Rich in Growth Factors (SRGF) can replace fetal bovine serum (FBS) to expand ASC by a clinical grade compliant protocol. The therapeutic potential of ASC is based also on their homing capacity toward inflammatory/cancer sites: oriented cell migration is a fundamental process in this scenario. We investigated the impact of SRGF on ASC migration properties. Methods. The motility/migration potential of ASC expanded in 5% SRGF was analyzed, in comparison to 10% FBS, by standard wound healing, bidimensional chemotaxis and transwell assays, and by millifluidic transwell tests. Mechanisms involved in the migration process were investigated by transient protein overexpression. Results. In comparison to standard 10% FBS, supplementation of the cell culture medium with 5% SRGF, strongly increased migration properties of ASC along the chemotactic gradient and toward cancer cell derived soluble factors, both in static and millifluidic conditions. We showed that, independently from applied migratory stimulus, SRGF expanded ASC were characterized by far lower expression of -smooth muscle actin (SMA), a protein involved in the cell migration machinery. Overexpression of SMA induced a significant and marked decrease in migration capacity of SRGF expanded ASC. In conclusion, 5% SRGF addition in the cell culture medium increases the migration potential of ASC, reasonably through appropriate downregulation of SMA. Thus, SRGF could potentially improve the therapeutic impact of ASC, both as modulators of the immune microenviroment or as targeted drug delivery vehicles in oncology.